Exploring Ethno-Religious Identity and its Impact on the Struggles of Democratic Consolidation in Nigeria's Fourth Republic - Mahmud IDREES Gana (International Studies Journal)
This paper explores ethno-religious identity and its impact on the struggles for democratic consolidation in Nigeria’s fourth republic. This study delves into the intricate dynamics of ethno-religious identity and its profound influence on the arduous path of democratic consolidation in Nigeria's Fourth Republic. Nigeria, characterized by its rich diversity of ethnic and religious groups, has grappled with the complexities of harnessing this diversity for democratic growth. Theoretically, the paper adopted the conflict trap. The paper employed a secondary method of data collection and analysis based on the collection of data from books, journals, and web-based materials, among others. The results revealed that ethno-religious identities contribute to the nation's unique character by providing a source of cultural richness and diversity. They also give people a sense of belonging and identity. When these identities, however, become politicized and instrumentalized, they can pose serious threats to democratic consolidation. The study concludes that ethno-religious identity is an integral part of Nigeria's social fabric and that its politicization can pose significant challenges to democratic consolidation. Addressing these challenges requires a multifaceted approach that promotes inclusive governance, civic education, and responsible leadership. Ultimately, a united and democratic Nigeria can thrive by embracing its diversity while transcending the divisive aspects of ethno-religious identity politics.